Pengaruh Penambahan Zat Aditif (Calcium Hypochlorite) Terhadap Coolant Properties (Viscosity) Minyak Sawit - Skp, Buma Gempa; Masnur, Dedy; HS, Irdoni (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Cutting fluid (coolant) are required in the machining processes. Most of cutting fluid are from mineral oil, and they are as unrenewable resource, therefore look for alternative resources ofmineral oil, which derived from vegetables oil. Palm oil have potency based of cutting fluid, however of coolant properties increased additive. This research want investigate effect ofadditive on phiysical properties of coolant. The method on mixture combining palm oil and additive (calcium hypochlorite) are conducted take of three proportion (95:5), (90:10), (85:15), the results from mixture the tested physical properties of viscosity at 40oC and 100oC of temperature. The results acknowledge the addition of (calcium hypochlorite) with palm oileffects on phiysical properties of coolant, the greater the percentage of calcium hypochlorite viscosity increased.Keywords: Cutting fluid (coolant), palm oil, additive, calcium hypochlorite, physical properties.